Pharmacological Blockade of Adenosine A2A but Not A1 Receptors Enhances Goal-Directed Valuation in Satiety-Based Instrumental Behavior - Li, Yan; Pan, Xinran; He, Yan; Ruan, Yang; Huang, Linshan; Zhou, Yuling; Hou, Zhidong; He, Chaoxiang; Wang, Zhe; Zhang, Xiong; Chen, Jiang-Fan (Frontiers in Pharmacology, 2018)
The balance and smooth shift between flexible, goal-directed behaviors and repetitive, habitual actions are critical to optimal performance of behavioral tasks. The striatum plays an essential role in control of goal-directed versus habitual behaviors through a rich interplay of the numerous neurotransmitters and neuromodulators to modify the input, processing and output functions of the striatum. The adenosine receptors (namely A2AR and A1R), with their high expression pattern in the striatum and abilities to interact and integrate dopamine, glutamate and cannabinoid signals in the striatum, may represent novel therapeutic targets for modulating instrumental behavior. In this study, we examined the effects of pharmacological blockade of the A2ARs and A1Rs on goal-directed versus habitual behaviors in different information processing phases of instrumental learning using a satiety-based instrumental behavior procedure. We found that A2AR antagonist acts at the coding, consolidation and expression phases of instrumental learning to modulate animals’ sensitivity to goal-directed valuation without modifying action-outcome contingency. However, pharmacological blockade and genetic knockout of A1Rs did not affect acquisition or sensitivity to goal-valuation of instrumental behavior. These findings provide pharmacological evidence for a potential therapeutic strategy to control abnormal instrumental behaviors associated with drug addiction and obsessive-compulsive disorder by targeting the A2AR.